2016
DOI: 10.4301/s1807-17752016000200002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Enterprise Architecture in Healthcare Organizations and Knowledge-Based Medical Diagnosis System

Abstract: Enterprise architecture (EA) is a tool that aligns organization's business-process with application and information technology (IT) through EAmodels. This EA model allows the organization to cut off unnecessary IT expenses and determines the future and current IT requirements and boosts organizational performance. Enterprise architecture may be employed in every firm where the firm or organization requires configurations between information technology and business functions. This research investigates the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…Zachman Framework merupakan salah satu framework EA yang diperkenalkan oleh Zachman untuk mendokumentasikan arsitektur pada suatu organisasi dari berbagai sudut pandang dan menunjukkan relasi antar komponen pada perusahaan [11]. Framework ini menyediakan struktur logical dalam pengembangan, integrasi, perancangan, pengelolaan, dan akses sistem informasi perusahaan [12].…”
Section: ) Zachman Frameworkunclassified
“…Zachman Framework merupakan salah satu framework EA yang diperkenalkan oleh Zachman untuk mendokumentasikan arsitektur pada suatu organisasi dari berbagai sudut pandang dan menunjukkan relasi antar komponen pada perusahaan [11]. Framework ini menyediakan struktur logical dalam pengembangan, integrasi, perancangan, pengelolaan, dan akses sistem informasi perusahaan [12].…”
Section: ) Zachman Frameworkunclassified
“…The NHI implementation requires combination, co-existence, and integration of various IS/IT solutions, such as software, hardware platforms, network protocols, and databases towards achieving its goals [8]. Interoperability is of paramount importance as medical data and information would be shared among different entities [31]. This is not without architectural deployment.…”
Section: Related Studiesmentioning
confidence: 99%
“…As shown in Figure 1, the ETA is defined as a four phase approach, which are objective, development, implementation, and strategic [12]. The deployment of the ETA can on iteration basis address the integration and interoperability problems in health care systems [31]. Figure 1 is discussed, with focus on the cruciality of the ETA in the implementation of the NHI.…”
Section: Enterprise Technical Architecturementioning
confidence: 99%
“…The findings demonstrated that EA adoption foster the alignment of IT and business goals in universities. Several studies have also highlighted EA adoption in the healthcare sector with important insights on how to implement similar EA in higher education [16] [17]. The overall conclusion from these studies is that every HEIs needs to focus on integrating the dimensions of people, processes, and technology [1].…”
Section: Related Workmentioning
confidence: 99%